Angiostrongylosis meningomyelitis without blood eosinophilia - Thanyalak Amornpojnimman; Nuttha Sanghan; Nichanan Ekpitakdamrong; Prut Koonalinthip; Sumonthip Leelawai; Pornchai Sathirapanya (Journal of Infection in Developing Countries)
Angiostrongylus cantonensis and Gnathostoma spinigerum usually cause eosinophilic meningitis with associated peripheral blood eosinophilia. A 44-year-old man developed acute paraplegia with bowel and bladder dysfunction. Spinal magnetic resonance images showed a long T2W hyperintensity signal from the 1st to 8th spinal thoracic level. Cerebrospinal fluid analysis revealed eosinophilia and elevated cerebrospinal fluid protein, whereas differential leucocytes count in peripheral blood was unremarkable. Positive immunoblot tests for A. cantonensis antibody in serum and cerebrospinal fluid were reported. The patient had neither history of recent traveling to the high endemic areas of the parasite in Thailand, nor consumption the parasitic hosts. Immediate treatment with intravenous pulse methylprednisolone and oral albendazole resulted in complete recovery. Despite an unremarkable differential leucocytes count, absence a history of parasitic hosts consumption, and a less common presentation with meningomyelitis, A. cantonensis should be considered when cerebrospinal fluid eosinophilia presents.